Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In trying to give the OP an elementary answer to this question, I made some rather stupid mistakes. I feel terrible about giving a wrong answer (in lieu of a complicated but correct one).

I devised a new proof, and wanted to check it before editing my answer. Does everyone like the following (well enough)?

Assertion: $$\lim_{x \to 0^+} \frac{x^{x^x}}{x} = 1$$

Proof: We pass to the log of the limit.

$$\log\left(\lim_{x \to 0^+} \frac{x^{x^x}}{x}\right) = \lim_{x \to 0^+} \log\left(\frac{x^{x^x}}{x}\right) = \lim_{x \to 0^+} \frac{\log(x)}{\frac{1}{x^x - 1}}$$

We use L'Hospital's rule, and rearrange:

$$\lim_{x \to 0^+} \frac{\log(x)}{\frac{1}{x^x - 1}} = \lim_{x \to 0^+} \frac{\frac{1}{x}}{\frac{-x^x(\log(x) + 1)}{(x^x - 1)^2}} = \lim_{x \to 0^+} \frac{- (x^x - 1)^2}{x^{x}(x\log(x) + x)} = \left( \lim_{x \to 0^+} \frac{-(x^x - 1)}{x^x} \right) \left( \lim_{x \to 0^+} \frac{(x^x - 1)}{x\log(x) + x} \right) $$

provided that both of these last limits exist; but (again using L'Hospital in the 2nd limit) we see that

$$\lim_{x \to 0^+} \frac{-(x^x - 1)}{x^x} = \frac{0}{1} = 0,$$

$$\lim_{x \to 0^+} \frac{(x^x - 1)}{x\log(x) + x} = \lim_{x \to 0^+} \frac{x^x(\log(x)+1)}{(1+ \log(x)) + (1)} = \left( \lim_{x \to 0^+} \frac{x^x(\log(x)+2)}{( \log(x)) + 2)} - \lim_{x \to 0^+} \frac{x^x}{(\log(x)) + 2)} \right) = 1,$$

and therefore $\displaystyle\log\left(\lim_{x \to 0^+} \frac{x^{x^x}}{x}\right) = 0$.

Evaluating both sides by $\exp(x)$ therefore shows that $\displaystyle\lim_{x \to 0^+} \frac{x^{x^x}}{x} = 1$.

share|cite|improve this question
Looks okay; I improved the formatting to make it a bit easier to read. – Brian M. Scott Jun 6 '12 at 0:43
The first equality after "but we see that" looks suspicious. You changed $1/\log(x)$ to $\log(x)$, which turns a nontrivial limit of type $0/0$ into a trivial one of type $0/\infty$... (And by the way, adding and subtracting one seems very roundabout; you could just replace $1$ by $\log(x)/\log(x)$.) – Hans Lundmark Jun 6 '12 at 8:32
@HansLundmark Thank you for catching those mistakes; I repaired the proof (yet again, and finally this time). – Chris Jun 6 '12 at 12:44
+1 for hard $\LaTeX$ work – draks ... Jul 9 '12 at 19:31
possible duplicate of Limit of $\frac{x^{x^x}}{x}$ as $x\to 0^+$ – Post No Bulls Dec 22 '13 at 5:27

The proof is correct, but you worked too hard. Shorter proof: $$\log \frac{x^{x^x}}{x}=\log x^{x^x-1}=(x^x-1)\log x=(e^{x\log x}-1)\log x\tag{1}$$ Recall that $\lim_{t\to 0}(e^t-1)/t =1$. Since $x\log x\to 0$ as $x\to 0$, it follows that $$\lim_{x\to 0^+} \frac{e^{x\log x}-1}{x\log x}=1$$ Rewriting (1) as $$ \left( \frac{e^{x\log x}-1}{x\log x}\right) \cdot (x\log^2x) $$ we see that the first factor tends to $1$ while the second tends to $0$. Thus, the limit of (1) is $0$, and the limit of $\frac{x^{x^x}}{x}$ is $1$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.